2021
DOI: 10.1017/s0958344021000082
|View full text |Cite
|
Sign up to set email alerts
|

What makes a good-quality language MOOC? An empirical study of criteria to evaluate the quality of online language courses from learners’ perspectives

Abstract: This paper focuses on quality assurance in language massive open online courses (LMOOCs). It is a qualitative study that adopts the grounded theory method and analyses evaluative comments on the quality of LMOOCs from learners’ perspectives. With the data collected from 1,000 evaluations from English as a second language (ESL) learners on China’s biggest MOOC platform “iCourse”, this study examines what has influenced learners’ perceptions of LMOOCs and identifies the specific quality criteria of five types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…As the main audience of MOOCs, learners' perceptions play a vitally important role in the success as well as the quality assurance of these courses (Luo and Ye, 2021). Despite this, most previous studies primarily consulted professors and course designers via interviews and surveys (Creelman and Ossiannilsson, 2014;Tong and Jia, 2017).…”
Section: Past Studies On Learners' Perspectives Of Moocsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the main audience of MOOCs, learners' perceptions play a vitally important role in the success as well as the quality assurance of these courses (Luo and Ye, 2021). Despite this, most previous studies primarily consulted professors and course designers via interviews and surveys (Creelman and Ossiannilsson, 2014;Tong and Jia, 2017).…”
Section: Past Studies On Learners' Perspectives Of Moocsmentioning
confidence: 99%
“…Despite this, most previous studies primarily consulted professors and course designers via interviews and surveys (Creelman and Ossiannilsson, 2014;Tong and Jia, 2017). Learners' voices were largely neglected in research on MOOC quality (Luo and Ye, 2021). This could be problematic because experts' views and course takers' could be different (Stracke et al, 2018).…”
Section: Past Studies On Learners' Perspectives Of Moocsmentioning
confidence: 99%
See 1 more Smart Citation
“…To make them comparable, the authors confined the six courses within undergraduate-level academic English courses. In choosing their sample, they adopted an approach similar to that used by Luo and Ye (2021): at the time of data collection, the chosen courses (a) were all among the top three courses on their respective sites by popularity, and (b) had been available to the public for at least two years. Details of the aims and enrollment numbers of each of these six courses are presented in Table 1.…”
Section: Samplementioning
confidence: 99%
“…By conducting descriptive statistical analysis in comparing two different courses in MOOC platform, Shukor and Abdullah's research suggested that using learning analytics in MOOC could help enhance the instructional design, thus improving the learning retention and engagement [13]. Focusing on quality assurance of language courses, Luo and Ye examined what has influenced learners' perceptions and identifies the specific quality criteria of five types of them with the data collected from English as a second language learners on China's biggest MOOC platform "iCourse" through qualitative study [14].…”
Section: Introductionmentioning
confidence: 99%